2020
DOI: 10.3389/fcimb.2020.00035
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Promyelocytic Leukemia Nuclear Bodies During HPV Infection

Abstract: Promyelocytic leukemia (PML) nuclear bodies (NBs) are highly dynamic subnuclear structures. Their name giving major component, PML protein, is essential for their formation. PML is present in many different isoforms due to differential splicing, which seem to contribute differently to PML NBs function. Sp100 and DAXX are also permanently residing in these structures. PML NBs disassemble in mitosis to form large cytoplasmic aggregates and reassemble after completion of cell division. Posttranslational modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 94 publications
(126 reference statements)
1
24
0
Order By: Relevance
“…Previous studies with HeLa cells reported that recombinant RGS14 translocates from the cytosol to the nucleus following mild heat stress (26). There, RGS14 localized to promyelocytic leukemia (PML) bodies, which have been implicated in cellular processes such as apoptosis, transcriptional regulation, DNA repair and replication (50). However, we have not observed native RGS14 localization at PML bodies in mouse hippocampal neurons, monkey striatal neurons (31), or rat B35 neuroblastoma cells (27), suggesting RGS14 PML body localization may be limited to unnatural host or non-neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with HeLa cells reported that recombinant RGS14 translocates from the cytosol to the nucleus following mild heat stress (26). There, RGS14 localized to promyelocytic leukemia (PML) bodies, which have been implicated in cellular processes such as apoptosis, transcriptional regulation, DNA repair and replication (50). However, we have not observed native RGS14 localization at PML bodies in mouse hippocampal neurons, monkey striatal neurons (31), or rat B35 neuroblastoma cells (27), suggesting RGS14 PML body localization may be limited to unnatural host or non-neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The initiation of VRCs of DNA viruses occurs at sites near PML-nuclear bodies. Human papillomavirus (HPV) infection requires the presence of PML protein suggesting that PML bodies are essential to establish infection [ 133 , 134 ]. However, Sp100 and DAXX, which act as transcriptional repressors, restrict viral gene expression in ADV [ 135 ], HPV [ 136 ], HSV-1 [ 137 ], and HCMV [ 138 ] infections.…”
Section: Interplay Between Viral Ibs and Innate Immunitymentioning
confidence: 99%
“…HCMV IE1 binds to PML in a complex with ISGF3 to impede IFN-I signaling [ 90 ]. In contrast, HPV requires PML nuclear bodies to establish infection [ 214 ]. Other examples for viral targeting PML include that EMCV 3C protease promotes PML degradation [ 215 ] and that the rabies virus phosphoprotein P and its truncated mutants cause the redistribution of PML-NBs into the cytoplasm [ 216 ].…”
Section: Viral Strategies To Subvert Trim-mediated Ifn-i Regulatormentioning
confidence: 99%